(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
Nowadays, globalization threatens to change the family relations and culture of our people through social networks, especially our religious, national and universal values, mentality, traditions and customs. The main reason for this is that the process of globalization introduces new ideas and views into the ideological landscape of the world. The article analyzes changes in Uzbek family relations under the conditions of globalization and their negative impact on youth education